Immunoserological Diagnosis of Human Borrelioses: Current Knowledge and Perspectives - Talagrand-Reboul, Emilie; Raffetin, Alice; Zachary, Pierre; Jaulhac, Benoît; Eldin, Carole (Frontiers in Cellular and Infection Microbiology, 2020)
Spirochetes of the genus Borrelia are divided into relapsing fever borreliae and Lyme disease borreliae. Immunoserological assays have been poorly developed for relapsing fever borreliae, where direct detection methods are more adapted to the pathophysiology of these infections presenting with massive bacteraemia. However, emergence of the novel agent of relapsing fever B. miyamotoi has renewed interest in serology in this context. In Lyme disease, because direct detection methods show low sensitivity, serology plays a central role in the diagnostic strategy. This diagnostic strategy is based on a two-tier methodology involving a first test (ELISA) with high sensitivity and acceptable specificity and a second, more specific test (western blot) for diagnostic confirmation. The most frequent limitations and pitfalls of serology are cross reactions, false IgM positivity, a seronegative window period at the early time of the infection, and serologic scars with a suspicion of reinfection. International guidelines have thus been proposed to avoid these difficulties with interpretation. Finally, unconventional diagnostic tests have been developed recently in the context of a highly publicized disease, with widely varying results, some of which have no available evidence-based data. New two-tier testing strategies using two ELISA tests (C6 and WCS for example) to replace immunoblot are currently proposed by some authors and guidelines, and promising new tests such as CXCL-13 in CSF are promising tools for the improvement of the diagnosis of Lyme borreliosis.